Conditions associated with circulating tumor-associated folate receptor 1 protein in healthy men and women. - Linda E Kelemen (Public Library of Science (PLoS), 2014)
Background Serum concentrations of the tumor-associated folate receptor 1 (FOLR1) protein may be a marker for early cancer detection, yet concentrations have also been detected in cancer-free women. We investigated the conditions associated with circulating FOLR1 protein in healthy individuals and sought to clarify the range of normal serum values. Methods Sera of cancer-free men and women (N = 60) enrolled in a population-based cohort study in Alberta, Canada were analyzed for FOLR1 protein using an electrochemical luminescence immunoassay. Dietary, lifestyle, medical and reproductive history information was collected by questionnaires. Differences in serum FOLR1 concentrations between groups were assessed by non-parametric tests, and predictors of serum FOLR1 concentrations were estimated using multivariable linear regression. Results Median serum FOLR1 concentration was higher in women (491 pg/ml, range = 327-693 pg/ml) than in men (404 pg/ml, range = 340-682 pg/ml), P = 0.001. FOLR1 concentration was also positively associated with vitamin A intake (P = 0.02), and showed positive trends with age and with oral contraceptive hormone use among women and an inverse trend with body mass index. All variables examined explained almost half of the variation in serum FOLR1 (model R2 = 0.44, P = 0.04); however, the retention of gender (P = 0.003) and vitamin A intake (P = 0.03) together explained 20% (P = 0.001) of serum FOLR1 variation. No other predictor was significant at P<0.05. Conclusions The positive association between serum FOLR1 concentration and female gender independent of an age effect suggests caution against statements to exploit serum FOLR1 for early cancer detection without further understanding the biological underpinnings of these observations. Serum FOLR1 concentrations may be influenced by the steroid retinoic acid (vitamin A) but do not appear to be associated with folate nutritional status. These findings require confirmation in larger independent studies.